The Influence of Bandwagon Effect, Viral Marketing, and Hedonic Motivation on Impulsive Buying Behavior for Skincare Products on TikTok - Aura Nabila; Alwiya Afwa (Institut Teknologi dan Bisnis Asia Malang, 2026)
This study aims to analyze the influence of bandwagon effect, viral marketing, and hedonic motivation on impulsive buying behavior of skincare products on TikTok Shop. This study uses a quantitative approach with a survey method of 100 respondents in Pekanbaru City who meet the criteria: actively using TikTok for at least 1 hour per day, having purchased skincare products from TikTok Shop, and being exposed to viral content or live streaming promotions. Data were analyzed using multiple linear regression. The results indicated that the bandwagon effect has a positive and significant effect on impulsiveness; viral marketing has a positive and significant effect on impulsive buying; hedonic motivation has a positive and significant effect on impulsive buying; and the three variables simultaneously have a significant effect on impulsiveness. The study’s results must be interpreted cautiously because online data collection via Google Forms may cause self-selection and non-response bias, limiting representativeness among Pekanbaru TikTok Shop users. Future research should expand the population and location beyond Pekanbaru to improve generalizability and adopt mixed methods by combining quantitative and qualitative approaches to gain more profound insights into consumer psychology and motivation.